Investigation on Heat Transfer Enhancement in Microchannel Using Al2O3/Water Nanofluids. (14th September 2021) - Munimathan, Arunkumar; Sathish, T.; Mohanavel, V.; Karthick, Alagar; Madavan, R.; Subbiah, Ram; Masi, Chandran; Rajkumar, S.
Abstract : Nowadays, reducing heat generation in electronic devices while using microchannel cooling is used to solve this problem. Because the trend is globally marching toward the compact size, the component's dimensions get smaller, but the warmth involved within the component increases. Studies of heat transfer rate are conducted to determine the effect of a fully heated microchannel conductor's heat transfer performance. Experiments are performed using nanofluid Al2 O3 /water through a concentration percentage of 0.1% and 0.25% and deionized water through a microchannel conductor with 25 rectangular microchannel numbers with a dimension of (0.42 × 0.42 × 100 ) mm 3 . This present work deals with the effect of nanofluids and their concentration percentages. Finally, it concluded that better heat transfer performance was seen in nanofluids compared to deionized water. The reason is the high viscosity of nanofluid Al2 O3 /water due to these nanoparticles is deposited on the wall surface of the microchannel and outcomes trendy improvement in the heat transfer. Finally, a high concentration percentage of nanofluids revealed a practical improvement in the transfer of microchannel. As a result, 0.25% of the concentration percentage achieved a satisfactory result compared to the remaining fluids and almost 32.5% and 26% of thermal resistance decrease.